2015
DOI: 10.7314/apjcp.2015.16.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Intronic Polymorphisms of the SMAD7 Gene in Association with Colorectal Cancer

Abstract: Based on genome-wide association studies (GWAS) a linkage between several variants such as single nucleotide polymorphisms (SNPs) in intron 3 of SMAD7 (mothers against decapentaplegic homolog7) were, rs12953717, rs4464148 and rs4939827 has been noted for susceptibility to colorectal cancer (CRC). In this study we investigated the relationship of rs12953717 and rs4464148 with risk of CRC among 487 Iranian individuals based on a casecontrol study. Genotyping of SNPs was performed by PCR-RFLP and for confirming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As one of the key effectors of TGF-β signaling, perturbation of SMAD7 expression has been documented to influence CRC progression [7][27]. Though the functional role of the SMAD7 polymorphisms (rs4464148, rs4939827, and rs12953717) has not yet been interpreted, a number of published epidemiological studies have reported that these polymorphisms are correlated with the risk of developing multiple cancers [12, 28, 29]. However, other studies have reported that these polymorphisms are not associated with cancer development [1720].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the key effectors of TGF-β signaling, perturbation of SMAD7 expression has been documented to influence CRC progression [7][27]. Though the functional role of the SMAD7 polymorphisms (rs4464148, rs4939827, and rs12953717) has not yet been interpreted, a number of published epidemiological studies have reported that these polymorphisms are correlated with the risk of developing multiple cancers [12, 28, 29]. However, other studies have reported that these polymorphisms are not associated with cancer development [1720].…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 30 Furthermore, there seems to exist strong associations between gene polymorphisms in CASC8 (rs7837328, rs7014346, rs6983267, rs10505477), SMAD7 (rs4939827, rs4464148, rs12953717), and an increased risk of CRC. 8 , 17 , 31 37 However, the correlation between these gene polymorphisms and the susceptibility to CRC is still unclear due to various conclusions drawn by individual studies.…”
Section: Discussionmentioning
confidence: 99%
“…After dropping studies that were not eligible for HWE (n = 10), a totally of 62 case-control studies were subsequently incorporated, 37 of which focused specifically on the connection between the rs4939827 and the chance of CRC, [7,8,[14][15][16][17][18][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] while the number of studies examining the connection between rs4464148 and rs12953717 and CRC risk were 10 and 15, respectively. [7,[23][24][25][26][27]29,30,38,39,[41][42][43][44] The above process can be understood more intuitively from Figure 1.…”
Section: Screening Processmentioning
confidence: 99%